PENGARUH LAMA PENYINARAN UV-C PADA BIJI CABAI RAWIT(CAPSICUM FRUSTESCENT L) TERHADAP LAJU PERTUMBUHAN TANAMAN, KADAR KLOROFIL-A DAN KERAPATAN STOMATA DAUN SERTA KADAR KAPSAISIN BUAH CABAI RAWIT - Restia Pranagari, R.A; Rupiasih, Ni Nyoman; Suyanto, Hery (BULETIN FISIKA; Vol 15 No 2 (2014): BULETIN FISIKA, 2014)
While irradiation of UV-C light has an effect on plant height, plant growth until the generative phase, chlorophyll-a content, stomatal density and concentration capsaicin chilies. Sample treatment on seeds / seedlings to ultraviolet C radiation (UV-C) respectively for 5 minutes, 15 minutes, 25 minutes, 30 minutes, 35 minutes, 50 minutes, 1 hour, 2 hours, 6 hours, 8 hours, 24 hours and 48 hours. The results showed that the effect of ultraviolet-C irradiation on seed negative effect on the inhibition of germination of the vegetative phase. While the generative phase, the plant that gets the least amount of UV radiation dose stunted. Ultraviolet radiation on seed very negative effect on the levels of chlorophyll-a. Chlorophyll-a levels were at least 5 minutes in sample treatment (S1). Stomatal density of cayenne pepper plant seeds treated with UV-C irradiation had a greater stomatal density than the untreated plants. Capsaicin levels which are most numerous in the old bean chili with UV-C irradiation 2 hours (S8) is an average of 755.17 mg / L each of chilies.